Improved Likelihood Ratio Tests for Cointegration Rank in the VAR Model - H. Peter Boswijk; Michael Jansson; Morten Ø. Nielsen (Tinbergen Institute, 2012)
We suggest improved tests for cointegration rank in the vector autoregressive (VAR) model and develop asymptotic distribution theory and local power results. The tests are (quasi-)likelihood ratio tests based on a Gaussian likelihood, but of course the asymptotic results apply more generally. The power gains relative to existing tests are due to two factors. First, instead of basing our tests on the conditional (with respect to the initial observations) likelihood, we follow the recent unit root literature and base our tests on the full likelihood as in, e.g., Elliott, Rothenberg, and Stock (1996). Secondly, our tests incorporate a 'sign' restriction which generalizes the one-sided unit root test. We show that the asymptotic local power of the proposed tests dominates that of existing cointegration rank tests.
Keywords: C12; C32; 330; Cointegration rank; efficiency; likelihood ratio test; vector autoregression; Kointegration; Statistischer Test; VAR-Modell; Theorie